1992
DOI: 10.1007/bf00974581
|View full text |Cite
|
Sign up to set email alerts
|

Autoradiographic study on [3H]flunitrazepam binding in rat cortex and hippocampus after chronic ethanol treatment

Abstract: Ethanol alters almost all membrane functions, but it behaves essentially like a benzodiazepine-type GABAergic agonist. The mechanism by which ethanol affects the GABA/benzodiazepine complex is not clear. We studied the possible changes in [3H]flunitrazepam binding induced by chronic ethanol treatment, using light microscopic autoradiography, to try to elucidate the controversy underlying this topic. This technique allows us to measure densities of benzodiazepine receptors in different anatomical brain areas--v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
3
0

Year Published

1992
1992
2000
2000

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 26 publications
1
3
0
Order By: Relevance
“…In a preliminary study (Negro et al, 1992), we did not find statistically significant differences between control and chronically ethanol-treated rats for the binding of benzodiazepine to areas from cortex and hippocampus, in agreement with results published by other groups using similar experimental conditions (Liljequist and Tabakoff, 1985;Tamborska and Marangos, 1986). In this report we confirm and extend those studies.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In a preliminary study (Negro et al, 1992), we did not find statistically significant differences between control and chronically ethanol-treated rats for the binding of benzodiazepine to areas from cortex and hippocampus, in agreement with results published by other groups using similar experimental conditions (Liljequist and Tabakoff, 1985;Tamborska and Marangos, 1986). In this report we confirm and extend those studies.…”
Section: Discussionsupporting
confidence: 93%
“…It is known that ethanol enhances the GABAA receptor complex-mediated C1-influx (Ticku et al, 1986;Glowa et al, 1989). Although chronic ethanol administration does not noticeably change the KD or B,,, for [3H]flunitrazepam (Liljequist and Tabakoff, 1985;Tamborska and Marangos, 1986;Negro et al, 1992), some reports have suggested that it could modify the modulation of benzodiazepine binding produced by GABA (de Vries et al, 1987;Hillmann et al, 1988). In the present work we studied the effect of chronic ethanol treatment on the modulation of [3H]flunitrazepam binding by GABA in cortical and hippocampal areas from rat brain.…”
mentioning
confidence: 99%
“…The changes in cerebellar mRNA levels observed in the present in situ hybridization experiments do, however, support earlier northern and immunoblot studies showing that chronic ethanol exposure down-regulates the a, subunit (Morrow et al ., 1990(Morrow et al ., , 1992Montpied et al ., 1991 ;Mhatre and Ticku, 1992 ;Mhatre et al, 1993) . The observed decrease in [ 3H]flunitrazepam binding is in agreement with the downregulation of the a, subunit ; however, although previous studies have shown similar decreases (Freund, 1980;Volicer and Biagioni, 1982), others have found that [ 3H]flunitrazepam binding remains unchanged following chronic ethanol treatment (Karobath et al ., 1980;Rastogi et al, 1986;Buck and Harris, 1990b ;Mhatre and Ticku, 1992 ;Negro et al ., 1992) . One possibility for this discrepancy may be that chronic ethanol administration increases the proportion of receptors that become internalized to an intracellular compartment, without changing the total number per cell.…”
Section: Gabaa /Bz Receptor Subunit Expression After Acute Ethanol Admentioning
confidence: 99%
“…Control animals belonging to the same litter as the ethanol-treated ones were pair-fed but were given plain water instead of the ethanol solution . Curves of growth, food, drink consumption, and blood ethanol level were monitored throughout treatment (Negro et al ., 1992b) . The experimental protocols involving laboratory animals were approved by the institutional review committee of the University of Leon and meet the guidelines of our responsible governmental agency .…”
Section: Animalsmentioning
confidence: 99%